PENGARUH DUKUNGAN KELUARGA PENDERITA TUBERCULOSIS (TB) TERHADAP HARGA DIRI PENDERITA TUBERCULOSIS (TB) DI PUSKESMAS OEBOBO KOTA KUPANG - Appolonaris Tomas Berkanis (Universitas Citra Bangsa, 2019)
ABSTRACT Background: Tuberculosis (TB) is a direct infectious disease caused by TB microbe (Mycobacterium Tuberculosis). TB more often attacks those who are in the productive age (15 – 50) that causes a productivity declining. And then, it will effect also to the self-respect of tuberculosis patient. The selfrespectcomes from oneself and others by being loved, respected, and appreciated. The family support can be understood as an effort from someone to motivate others morally and materially in doing their activity. This research classifies four kinds of family support: Appreciation Support, Instrumental Support, Informational Support, and Emotional Support. Aim: The aim of this research is to know the influence of influence of family support of tuberculosis patient to the self-respect of tuberculosis patient. Methods: This research employs Analytic Research Design, especially descriptive analytic with cross sectional design. The data were taken from 31 respondents by using questionnaires. Result: Based on the contingency coefficient test, it is showed that there is a significant influence of family support to the self-respect of tuberculosis patient (0,000 < 5%, α = 0,05). Therefore, H1 is accepted, While H0 is rejected since the results shows that there is an influence of family support of tuberculosis patient to the self-respect of tuberculosis patient in Puskesmas Oebobo, Kupang. Key words: Tuberculosis (TB), Family Support, Self-Respect, TB Patient